Understanding the importance of non-material factors in retaining community health workers in low-income settings: a qualitative case-study in Ethiopia. Issue 10 (8th October 2020) - Arora, Nikita; Hanson, Kara; Spicer, Neil; Estifanos, Abiy Seifu; Keraga, Dorka Woldesenbet; Welearegay, Alemtsehay Tewele; Tela, Freweini Gebrearegay; Hussen, Yemisrach Ahmed; Mandefro, Yordanos Semu; Quaife, Matthew
Abstract : Objectives: The motivation and retention of community health workers (CHWs) is a challenge and inadequately addressed in research and policy. We sought to identify factors influencing the retention of CHWs in Ethiopia and ways to avert their exit. Design: A qualitative study was undertaken using in-depth interviews with the study participants. Interviews were audio-recorded, and then simultaneously translated into English and transcribed for analysis. Data were analysed in NVivo 12 using an iterative inductive-deductive approach. Setting: The study was conducted in two districts each in the Tigray and Southern Nations, Nationalities and People's Republic (SNNPR) regions in Ethiopia. Respondents were located in a mix of rural and urban settings. Participants: Leavers of health extension worker (HEW) positions (n=20), active HEWs (n=16) and key informants (n=11) in the form of policymakers were interviewed. Results: We identified several extrinsic and intrinsic motivational factors affecting the retention and labour market choices of HEWs. While financial incentives in the form of salaries and material incentives in the form of improvements to health facility infrastructure, provision of childcare were reported to be important, non-material factors like HEWs' self-image, acceptance and validation by the community and their supervisors were found to be critical. A reduction or loss of these non-material factors proved to be the catalyst for many HEWs to leave their jobs. Conclusion: Our study contributes new empirical evidence to the global debate on factors influencing the motivation and retention of CHWs, by being the first to include job leavers in the analysis. Our findings suggest that policy interventions that appeal to the social needs of CHWs can prove to be more acceptable and potentially cost-effective in improving their retention in the long run. This is important for government policymakers in resource constrained settings like Ethiopia that rely heavily on lay workers for primary healthcare delivery.